Doubling back of Foley catheter in urethra in a tetraplegic patient: delayed recognition. (5th November 2014) - Subramanian, Vaidyanathan; Soni, Bakul; Hughes, Peter; Singh, Gurpreet
Abstract : A 51-year-old man with C-6 tetraplegia had ureteric calculi, developed ureteric stricture and required bilateral nephrostomy. Following change of the left nephrostomy, bloody urine was drained per nephrostomy. The urethral catheter was also changed; bloody drainage per urethral catheter was attributed to blood seeping from the left kidney. The length of the Foley catheter outside the penis appeared correct; therefore, it was presumed that the catheter had been introduced into the bladder. The following day, bladder washout could not be performed due to blockage of the catheter. CT of the kidneys and bladder revealed doubling back of the Foley catheter in the bulbar urethra with the balloon inflated in the urethra. The urethral catheter was removed and another catheter inserted satisfactorily by a senior doctor. From this experience we learned that a 'Long Catheter Sign' will not be positive if the catheter doubles back in the urethra. When in doubt, imaging studies should be performed immediately to check the position of the Foley catheter.